The consequences of protecting audit partners’ personal assets from the threat of liability - Lennox, Clive S. (2013)
This study investigates the audit firm’s decision to protect its partners’ personal assets by becoming a limited liability partnership (LLP). We find that the likelihood of an audit firm switching from unlimited to limited liability is increasing in its size and exposure to litigation risk. We find no evidence that audit firms supply lower audit quality, lose market share, or charge lower audit fees after they become LLPs. However, the mix of public and private clients in audit firms’ portfolios exhibits a significant shift toward riskier publicly traded companies after the switch to limited liability.